Interdecadal Foredune Changes along the Southeast Australian Coastline: 1942–2014 - Thomas B. Doyle; Andrew D. Short; Peter Ruggiero; Colin D. Woodroffe (Journal of Marine Science and Engineering, 2019)
Foredunes are important features within coastal landscapes, yet there are relatively few medium to long-term studies on how they evolve and change over time. This study of Australia’s New South Wales (NSW) foredunes has used 70 years of aerial photographs (or photogrammetry) and recent Light Detection and Ranging (LiDAR) datasets to assess multi-decadal fluctuations in foredune morphology. It was shown that over the past 70 years NSW foredunes have exhibited considerable spatial variation, ranging from accretion/aggradation to recession. Those sites that accreted predominantly extended seaward as new incipient dunes, gaining a maximum of 235 m3 m−1 in sand volume over the study period (for the entire dune system). These sites were commonly found in the north of the state, within closed sediment compartments, and with strong onshore (and alongshore) wind climates present (increasing the potential for aeolian sand transport). Stable foredunes were those that remained within +/− 50 m3 m−1 of their initial volume and managed to recover from the various storm impacts over the study period. The majority of these sites were found within the central to southern half of the state, behind embayed beaches, and within leaky sediment compartments, or those that have estuarine sinks. Finally, those foredunes in recession have retreated landwards and/or have reduced in height or width, and lost up to 437 m3 m−1 of sand volume over the study period. There was no clear spatial trend for these sites; however, generally they were found in compartments that had unusual orientations, had disruptions in longshore drift/cross shore sand delivery (i.e., rocky reefs), or were being impacted by humans (i.e., the installation of river training walls, sand bypassing systems, or coastal management programs). This study has shown that NSW foredunes have undergone substantial recent changes and, by understanding their past history, will provide better insight into how they can be managed into the future.